Evaluation of mindful eating, body image and anthropometric measurements of adolescents during the COVID-19 pandemic - YILMAZ, Birsen; GEZMEN KARADAĞ, Makbule (Progress in Nutrition, 2022)
Objective: Body dissatisfaction is an increasing problem in adolescents, and it is thought that mindful eating and body image are related. These problems have become more serious during the pandemic period. This current study was carried out to examine the relationship between adolescents' mindful eating, body image, and anthropometric measurements during COVID-19 pandemic.Methods: A total of 200 adolescents (100 boys and 100 girls) aged 11-17 years, were involved in the study. The data were collected by the researcher using the face-to-face interview method through a questionnaire. The Mindful Eating Questionnaire was used to determine mindful eating. The Stunkard body image scale was employed to evaluate the body image of individuals, and all anthropometric measurements were made by the researcher in accordance with technique.Results: The mean age of the individuals was 14.2±2.04 years, and more than half (52%) attended high school. 60.0% of obese boys and 38.0% of obese girls considered themselves obese. A statistically significant difference was found depending on gender in terms of body perception (p0.05). A negative statistically significant correlation was determined between the total mindful eating score of those who described themselves as underweight, overweight, and obese, and BMI (kg/m2), waist circumference (cm), hip circumference (cm), and body fat (%) (p